Flint tools from the present tidal zone, Lussa Bay, Isle of Jura, Argyll - Mercer, John (Proceedings of the Society of Antiquaries of Scotland, 1973)
NR 643868. 4424 flint artefacts were collected from the tidal zone of Lussa Bay, of which 1064 were identifiable; the assemblage is dominated by blades, flakes partly backed with cortex, cores, scrapers and leaf-shaped flakes, but includes microliths and microburins. Comparison with the collection from Lealt Bay, Jura, indicates that the majority of the Lussa Bay material is earlier and belongs to the Boreal-Atlantic transition (c 5500 BC); an ancestry in the mainland British Upper Palaeolithic is argued. There is also a separate Late Atlantic (Neolithic) phase of activity. A R